Optimization of the Implementation of Occupational Health and Safety (K3) Standards - Sofyan, Mhd Taupik; Susilawati, Susilawati; Gurning, Fitriani Pramita (Indonesian Journal of Global Health Research, 2024)
Implementation of K3 standards is very important in every agency, especially at the lowest level of health facilities, namely community health centers. In accordance with Minister of Health Regulation No. 52 of 2018 concerning Occupational Safety and Health in Health Facilities, it is stated that every Health Fasyan is obliged to implement occupational safety and health efforts. The implementation of health center K3 is expected to reduce the number of accidents for workers. So that the safety and health of staff is guaranteed, services can be improved for patients at the health center. The Community Health Center Occupational Health and Safety Guidelines cover various aspects such as Occupational Health and Safety policies, risk management, planning, controlling and implementing K3. The implementation of K3 in community health centers is very influential in improving the quality of community health centers. Therefore, employees or people who work there must implement an K3 program. This research involved community health center officers in Pamatang Sidamanik, Simalungun Regency, North Sumatra Province. This research aims to find out how the Pamatang Sidamanik Community Health Center implements K3 standards. This research uses a quantitative methodology with a cross sectional design. The population in this study were community health center officers in Pamatang Sidamanik, totaling 40 respondents. From the total population obtained, the sample that the researcher took was the total of that population, because the researcher used a total sampling technique. Primary data collected directly by researchers through questionnaires from previous research. The Ministry of Health Regulatory Indicator is a questionnaire used by researchers. The results of the bivariate statistical test using Chi Square show that the average p-value is 0.000 (<0.05), so that Ho is rejected and Ha is accepted, this means that the implementation of K3 standards at the Pamatang Sidamanik health center is running optimally. The implementation of the K3 program in community health centers greatly influences both the quality and accreditation of community health centers. Researchers hope that the agencies studied will continue to evaluate the implementation of K3 and continue to run optimally. Suggestions for every health facility, especially the Pamatang Sidamanik health center, to increase the implementation of Occupational Safety and Health.